HR’s Role in Managing Employee Expectations During an Acquisition: A Case Study Approach - Pankaj Kumar, Riddhi Doshi (2010)
It would be agreed that HR, leadership, culture and communication all have contributory and overlapping roles to play in the success of an acquisition. This study attempts to explore the role of HR in greater depth. Commencing with the structure of the HR department within ACons, we come to understand the hype behind the trend in mergers and acquisitions as inorganic modes of growth being employed by companies. With HR being accountable towards the success and factors of acquisitions, we proceed to appreciate the role of HR within organizations where it differentiates between operational and strategic purposes and how this contributes to the overall performance of the organization. Using Ulrich’s model, HR as a function involves four simultaneous roles – Strategic Partner, Administrative Expert, Employee Champion and Change Agent. Our study then continues to explore the interconnected relationship between HR, psychological contract of employees and the organization’s business strategies. Based on how these psychological contracts are maintained and if there is a breach or violation, there can be a positive and negative impact to the organization. Schuler and Jackson propose a three stage model of M&A which identifies HR’s role throughout the stages – (i) precombination, (ii) integration and (iii) solidification and advancement of the new entity. Data from the interviews is analysed on an emerging basis using Grounded Theory. Using open coding, axial coding and selective coding till a saturation point is reached, the story that emerges is analyzed to obtain an insight into how critical HR’s role is during ACons’ acquisition process.